Diseño conceptual de una planta de producción de bioetanol a partir del rastrojo de maíz en el departamento de Cundinamarca (2022)
In this project, the conceptual design of a bioethanol production plant was carried out in the department of Cundinamarca based on agro-industrial residues, in this case corn stover. From the bibliography, the characteristics of the raw material used were determined, such as its physicochemical characterization and energy potential. For the production of bioethanol, it was decided to carry out the process through a saccharification and fermentation reaction carried out simultaneously in order to extract the sugars still present in the corn stover. Pretreatment processes such as impregnation with sulfuric acid before the steam explosion were also used to help this release of sugars.